Záměrná nespolehlivost rozhodování - Roudný, Radim (Univerzita Pardubice, 2000)
Reliability of the decisionmaking is strongly influinced by reliability of the subject making the decisions. Sometimes the subject makes a wrong decision for purpose. One of the metods is numerical estimation of these reliabilies with the impact on the structure and control of an institution.
Keywords: Rozhodování; jistota; Riziko; nejistota; rozhodovací procesy